Development of the “Sehat Tanpa Depresi” Explainer Animation as a Mental Health Education Media for Adolescents - Permana, Fahmi Candra; Albari, Fardan Barkah; Sari, Intan Permata; Sylviani, Sisilia (Journal of Software Engineering, Information and Communication Technology (SEICT), 2025)
Going through a transitional time in their adolescence makes many Indonesians more susceptible to depression. When people do not realize how important mental health is, depression can grow in popularity. They can be a suitable way to explain what depression is. Many believe that using explainer animations helps share these messages interestingly and easily. This project plans to produce an explainer animation named “Sehat Tanpa Depresi” for teaching mental health to adolescents and to check how effective it is. Using the Design and Development (DD) approach with the N.J. Manson model, the research consisted of five parts: problem awareness, suggestions, product development, evaluation and conclusion. Experts tested and reviewed the developed media, finding it met 91.45% of the requirements, offered 91.11% proper media and was evaluated by 83.8% of users. According to these findings, the explainer animation works well and is suitable for teaching mental health to teenagers.